THE INFLUENCE OF SERVICE QUALITY ON COMMUNITY SATISFACTION IN THE MAKING OF E-KTP IN LUMAJANG REGENCY - Tomy Ernawati; Augusto da C Soares; Suwignyo Widagdo; Yuniorita Indah Handayani (MBA : Journal of Management and Business Aplication, 2021)
This study aims to determine the quality of services to community satisfaction for making E-KTP in Sumbersuko District, Lumajang Regency. This research was conducted in Sumbersuko District, Lumajang Regency. The population in this study is the people in Sumbersuko Subdistrict who already have E-KTP with totaling 27,306 people. The sampling method uses simple random sampling with questionnaire distribution techniques. The number of samples in this study was 125 respondents spread in Sumbersuko District. The method of data analysis in this study used multiple linear regression analysis with the help of SPSS 20.0 software. Based on the results of data analysis shows that the variable responsiveness, assurance, and empathy have a significant effect on community satisfaction with the value of the influence of respectively 27.3%, 30.5%, and 14.3%. While the tangible and reliability variables did not significantly influence community satisfaction in making E-KTP in Sumbersuko District, Lumajang Regency. This result also shows that the assurance variable is the most dominant variable influencing community satisfaction in making E-KTP in Sumbersuko District, Lumajang Regency.